### 1 Answer | Add Yours

You need to evaluate the following inequality, such that:

`x^3 + x^2 + 64x + 64 > 0`

You need to convert the inequality into an equation, such that:

`x^3 + x^2 + 64x + 64 = 0`

You may create two groups of terms to perform factorization, such that:

`(x^3 + x^2) + (64x+ 64) = 0`

You may factor out` x^2` and 64 such that:

`x^2(x + 1) + 64(x + 1) = 0`

You may factor out (x + 1), such that:

`(x + 1)(x^2 + 64) = 0`

Using the zero product rule yields:

`x + 1 = 0 => x = -1`

`x^2 + 64 > 0 for x in R`

You need to check what are x values that makes the inequality `(x + 1)(x^2 + 64) > 0` to hold. You need to remember that a product of two positive factors or two negative factors is positive.

Since `x^2 + 64 > 0` , hence `x + 1` needs to be also positive. You shoudl notice that `x + 1 > 0 ` for `x > -1` .

**Hence, evaluating the interval solution to the given inequality, yields **`x > -1 => x in (-1,oo).`

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes